Pelvic vs Lumbar Fusion in Neuromuscular Scoliosis - A Systematic Review - Soini, Venla; Karkkola, Sini; Raitio; Arimatias; Syvänen; Johanna; Helenius, Ilkka (United Kingdom, 2025)
Study Design
Systematic literature review.
Objectives
Posterior spinal fusion is the golden standard in the treatment of neuromuscular scoliosis. There are different views on whether pelvic fusion is necessary.
Methods
A systematic literature review according to PRISMA guidelines was performed. A total of 628 articles were screened. Original articles of neuromuscular scoliosis patients with reference to posterior spinal fusion in the population of ≤20 years of age were included. Operative technique with lumbar pedicle screws was required. Case reports, articles with missing data on pelvic parameters or with a postoperative follow-up of less than 2 years were excluded. A final of 29 original articles were included in the review.
Results
A total of 1611 patients undergoing posterior spinal fusion for neuromuscular scoliosis were included in the analysis with a mean age of 14.0 ± 1.0 years and a mean number of 15.5 ± 0.8 levels fused. Spinal fusion was extended to the pelvis in 1222 cases, while in 389 patients had fusion limited to the lumbar spine. The percentage of main curve correction was slightly higher in pelvic fusion patients 63 ± 10% compared to 58 ± 9% in lumbar fusion group, P < 0.001. Pelvic obliquity correction was superior in the pelvic fusion group, 58% compared to 42% in the spinal fusion group, P < 0.001. Operative time, complication rate and perioperative bleeding were greater in the pelvic fusion group.
Conclusions
Pelvic fusion in posterior spinal fusion for neuromuscular scoliosis results in small but statistically significant differences in curve correction and pelvic obliquity but increases the risk for perioperative bleeding and other complications. The impact on quality of life should be addressed in future research.